Aspirin in the prevention of pre‐eclampsia in high‐risk women: a randomised placebo‐controlled PREDO Trial and a meta‐analysis of randomised trials. Issue 1 (6th November 2012) - Villa, PM; Kajantie, E; Räikkönen, K; Pesonen, A‐K; Hämäläinen, E; Vainio, M; Taipale, P; Laivuori, H; ,
<x xml:space="preserve">Abstract</x> Objective To study the effect of aspirin in the prevention of pre‐eclampsia in high‐risk women. Design Randomised, double‐blinded, placebo‐controlled trial. Setting Maternity clinics in ten Finnish hospitals participating in the PREDO Project. Sample A total of 152 women with risk factors for pre‐eclampsia and abnormal uterine artery Doppler velocimetry. Methods Participants were randomised to start either aspirin 100 mg/day or placebo at 12 + 0 to 13 + 6 weeks + days of gestation. Because of the limited power of this trial, we also conducted a meta‐analysis of randomised controlled trials that included data on 346 women with abnormal uterine artery Doppler flow velocimetry, and aspirin 50–150 mg/day started at or before 16 weeks of gestation. Main outcome measure Pre‐eclampsia, gestational hypertension and birthweight standard deviation (SD) score. Outcome measures for the meta‐analysis were pre‐eclampsia, severe pre‐eclampsia, preterm (diagnosed <37 + 0 weeks of gestation) and term pre‐eclampsia. Results From the 152 randomised women, 121 were included in the final analysis. Low‐dose aspirin did not reduce the rate of pre‐eclampsia (relative risk [RR] 0.7, 95% CI 0.3–1.7); gestational hypertension (RR 1.6, 95% CI 0.6–4.2); early‐onset pre‐eclampsia (diagnosed <34 + 0 weeks of gestation) (RR 0.2, 95% CI 0.03–2.1); or severe pre‐eclampsia (RR 0.4, 95% CI 0.1–1.3); and the results were not statistically significant in an intention‐to‐treat analysis. However, our meta‐analysis, including the current data, suggested that low‐dose aspirin initiated before 16 weeks of gestation reduces the risk of pre‐eclampsia (RR 0.6, 95% CI 0.4–0.8) and severe pre‐eclampsia (RR 0.3, 95% CI 0.1–0.7). Conclusions Our trial showed no statistically significant effect of aspirin in preventing pre‐eclampsia in high‐risk women. However, our meta‐analysis suggested that aspirin may reduce the incidence of pre‐eclampsia.